A ceric ammonium nitrate based oxidative cleavage pathway for the asymmetric aldol adducts of oxadiazinones derived from (1R, 2S)-N-p-methoxybenzylnorephedrine. Issue 9 (15th September 2017) - Leise, Austin R.; Comas, Nicole; Harrison, Doug; Patel, Dipak; Whitemiller, Eileen G.; Wilson, Jennifer; Timms, Jacob; Golightly, Ian; Hamaker, Christopher G.; Hitchcock, Shawn R.
Graphical abstract: Abstract: An N 4 - p -methoxybenzyloxadiazinone has been prepared from (1 R, 2 S )-norephedrine through a process of reductive amination, N-nitrosation, reduction, and cyclization. The oxadiazinone was acylated and employed in the asymmetric aldol addition reaction with aromatic and aliphatic aldehydes to yield aldol adducts in isolated yields ranging from 54% to 90%. Selected aldol adducts were treated with ceric ammonium nitrate in aqueous acetonitrile to afford the desired β-hydroxycarboxylic acids through a tandem process of oxidative cleavage of the N 4 - p -methoxybenzyl group and acidic hydrolysis of the N 3 -acyl side chain. The β-hydroxycarboxylic acids were recovered in high diastereomeric purity as determined by 500 MHz 1 H NMR spectroscopy and the absolute configuration was confirmed by polarimetry. The chiral auxiliary unit, the 3, 4, 5, 6-tetrahydro-2 H -1, 3, 4-oxadiazin-2-one (oxadiazinone), was converted into its corresponding 3, 6-dihydro-2 H -1, 3, 4-oxadiazin-2-one (oxadiazinone) through an oxidative pathway promoted by the ceric ammonium nitrate. Abstract : (1 R, 2 S )- N - p -Methoxybenzyl- N -nitroso-norepehdrine: C17 H20 N2 O3 [ α ]D 23  = +100.4 ( c 0.58, CHCl3 ) Source of chirality: (1 R, 2 S )-norephedrine Absolute configuration: (1 R, 2 S ) Abstract : (1 R, 2 S )-2-(1-( p -Methoxybenzyl)hydrazinyl)-1-phenyl-1-propanol: C17 H22 N2 O2 [ α ]D 23  =  + 62.2 ( c 0.92, CHCl3 ) Source of chirality: (1 R, 2 S )-norephedrine Absolute configuration: (1 R, 2 S ) Abstract : (5 S, 6 R )-4-( p -Methoxybenzyl)-5-methyl-6-phenyl-2 H -1, 3, 4-oxadiazin-2-one: C18 H20 N2 O3 [ α ]D 23  = +62.7 ( c 1.01, CHCl3 ) Source of chirality: (1 R, 2 S )-norephedrine Absolute configuration: (5 S, 6 R ) Abstract : (5 S, 6 R )-4-( p -Methoxybenzyl)-5-methyl-6-phenyl-3-propanoyl-2 H -1, 3, 4-oxadiazin-2-one: C21 H25 N2 O4 [ α ]D 23  = −10.1 ( c 1.02, CHCl3 ) Source of chirality: (1 R, 2 S )-norephedrine Absolute configuration: (5 S, 6 R ) Abstract : (5 S, 6 R )-3-((2 S, 3 S )-3-Hydroxy-2-methyl-3-phenylpropanoyl)-4-(4-methoxybenzyl)-5-methyl-6-phenyl-1, 3, 4-2 H -oxadiazin-2-one: C28 H30 N2 O5 [ α ]D 23  = −5.9 ( c 0.16, CHCl3 ) Source of chirality: (1 R, 2 S )-norephedrine Absolute configuration: (5 S, 6 R )-3-(2 S, 3 S ) Abstract : (5 S, 6 R )-3-((2 S, 3 S )-3-( p -Chlorophenyl)-3-hydroxy-2-methyl-propanoyl)-4-(4-methoxybenzyl)-5-methyl-6-phenyl-1, 3, 4-2 H -oxadiazin-2-one: C28 H29 ClN2 O5 [ α ] 23  = −7.7 ( c 0.18, CHCl3 ) Source of chirality: (1 R, 2 S )-norephedrine Absolute configuration: (5 S, 6 R )-3-((2 S, 3 S ) Abstract : (5 S, 6 R )-3-((2 S, 3 S )-3-( p -Bromophenyl)-3-hydroxy-2-methyl-propanoyl)-4-(4-methoxy benzyl)-5-methyl-6-phenyl-1, 3, 4-2 H -oxadiazin-2-one: C28 H29 BrN2 O5 [ α ] 23  = −9.65 ( c 1.69, CHCl3 ) Source of chirality: (1 R, 2 S )-norephedrine Absolute configuration: (5 S, 6 R )-3-((2 S, 3 S ) Abstract : (5 S, 6 R )-3-((2 S, 3 S )-3-( o -Bromophenyl)-3-hydroxy-2-methylpropanoyl)-4-(4-methoxybenzyl)-5-methyl-6-phenyl-1, 3, 4-2 H -oxadiazin-2-one: C28 H29 BrN2 O5 [ α ]D 23  = −45.7 ( c 1.01, CHCl3 ) Source of chirality: (1 R, 2 S )-norephedrine Absolute configuration: (5 S, 6 R )-3-((2 S, 3 S ) Abstract : (5 S, 6 R )-3-((2 S, 3 S )-3-Hydroxy-2-methyl-3-( m -nitrophenyl)propanoyl)-4-(4-methoxybenzyl)-5-methyl-6-phenyl-1, 3, 4-2 H -oxadiazin-2-one: C28 H29 N3 O7 [ α ]D 23  = −12.2 ( c 1.06, CHCl3 ) Source of chirality: (1 R, 2 S )-norephedrine Absolute configuration: (5 S, 6 R )-3-((2 S, 3 S ) Abstract : (5 S, 6 R )-3-((2 S, 3 S )-3-Hydroxy-2-methyl-3-naphthylpropanoyl)-4-(4-methoxybenzyl)-5-methyl-6-phenyl-1, 3, 4-2 H -oxadiazin-2-one: C32 H33 N2 O5 [ α ]D 23  = −16.4 ( c 1.01, CHCl3 ) Source of chirality: (1 R, 2 S )-norephedrine Absolute configuration: (5 S, 6 R )-3-((2 S, 3 S ) Abstract : (5 S, 6 R )-3-((2 S, 3 R, E )-3-Hydroxy-2-methyl-5-phenyl-4-pentenoyl)-4-(4-methoxy benzyl)-5-methyl-6-phenyl-1, 3, 4-oxadiazin-2-one: C30 H33 N2 O5 [ α ]D 23  = +0.7 ( c 2.4, CHCl3 ) Source of chirality: (1 R, 2 S )-norephedrine Absolute configuration: (5 S, 6 R )-3-((2 S, 3 S ) Abstract : (5 S, 6 R )-3-((2 S, 3 R )-3-Hydroxy-2-methylhexanoyl)-4-(4-methoxybenzyl)-5-methyl-6-phenyl-1, 3, 4-oxadiazin-2-one: C25 H32 N2 O5 [ α ]D 23  = −0.02 ( c 1.0, CHCl3 ) Source of chirality: (1 R, 2 S )-norephedrine Absolute configuration: (5 S, 6 R )-3-((2 S, 3 R ) Abstract : (5 S, 6 R )-3-((2 S, 3 R )-3-Hydroxy-2, 5-dimethylhexanoyl)-4-(4-methoxybenzyl)-5-methyl-6-phenyl-1, 3, 4-oxadiazin-2-one: C26 H34 N2 O5 [ α ] 25 D  = +0.6 ( c 1.15, CHCl3 ) Source of chirality: (1 R, 2 S )-norephedrine Absolute configuration: (5 S, 6 R )-3-((2 S, 3 R ) Abstract : (5 S, 6 R )-3-((2 S, 3 R )-3-Hydroxy-2-methyldecanoyl)-4-( p -methoxybenzyl)-5-methyl-6-phenyl-1, 3, 4-oxadiazin-2-one: C29 H40 N2 O5 [ α ] 25 D  = +2.5 ( c 1.38, CHCl3 ) Source of chirality: (1 R, 2 S )-norephedrine Absolute configuration: (5 S, 6 R ) Abstract : (2 S, 3 S )-3-Hydroxy-2-methyl-3-phenylpropanoic acid: C10 H11 ClO3 [ α ]D 23  = −21.8 ( c 0.75, CH2 Cl2 ) Source of chirality: (1 R, 2 S )-norephedrine Absolute configuration: (2 S, 3 S ) Abstract : (2 S, 3 R )-3-Hydroxy-2, 5-dimethylhexanoic acid: C8 H16 O3 [ α ] 22 D  = +30.3 ( c 0.28, CH2 Cl2 ) Source of chirality: (1 R, 2 S )-norephedrine Absolute configuration: (2 S, 3 S ) Abstract : (6 R )-5-Methyl-6-phenyl-3, 6-dihydro-2 H -1, 3, 4-oxadiazin-2-one: C10 H10 N2 O2 [ α ] 24 D  = −192.5 ( c 1.08, CHCl3 ) Source of chirality: (1 R, 2 S )-norephedrine Absolute configuration: (6 R )